IMPLEMENTASI KEBIJAKAN KEWENANGAN ATRIBUTIF CAMAT DI KECAMATAN PRAYA, PUJUT, DAN JANAPRIA KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Lalu Budiman (Indonesian Journal of Dialectics, 2012)
The main problem of this research is district apparatus in District of Praya, Pujut, and Janapria Central Lombok Regency can not do better their job yet, although the government pass through legislation regulation gave attributive authority to district head for carry out it job. This research intend for investigate, watch closely and analyze that the policy implementation of district head attributive authority that implement by district apparatus. Hoping from the result of analysis has a new concept about public policy implementation.            The used of theory is the policy implementation theory of Mazmanian and Sabatier. This research used qualitative method and qualitative descriptive research design. The most instrument of this research is the researcher. The resources of data are document, archives, interview, observation and office equipment, used to get data and information at the field. While, the method of collecting data used interview, observation and document.            The result of this study showed that the policy of District Head Attributive Authority in District of Praya, Pujut, and Janapria Central Lombok Regency West Nusa Tenggara Province can not good implementation, so that not able to improved of carrying out of apparatus district job.  This research found new concept that the success of implementation of atributive authority can achieved through improvement on will and ability from receiver of authority, and there is political will from giver of authority. Because of that, attributive authority can implementation by receiver of authority effectively.